Selective orbital imaging of excited states with x-ray spectroscopy: the example of α-MnS - Amorese, Andrea; Leedahl, B.; Sundermann, M.; Gretarsson, H.; Hu, Z.; Lin, H.-J.; Chen, C. T.; Schmidt, M.; Borrmann, H.; Grin, Yu.; Severing, A.; Haverkort, Maurits W.; et al. (Physical review. X, Expanding access, 2021)
Herein we show that nonresonant inelastic x-ray scattering involving an s core level is a powerful spectroscopic method to characterize the excited states of transition metal compounds. The spherical charge distribution of the s core hole allows the orientational dependence of the intensities of the various spectral features to produce a spatial charge image of the associated multiplet states in a straightforward manner, thereby facilitating the identification of their orbital character. In addition, the s core hole does not add an extra orbital angular momentum component to the multiplet structure so that the well-established Sugano-Tanabe-Kamimura diagrams can be used for the analysis of the spectra. For α-MnS we observe the spherical charge density corresponding to its high-spin 3d5 (6A1) ground state configuration and we were able to selectively image its excited states and identify them as t2g (5T2) and eg (5E) with an energy splitting 10Dq of 0.78 eV.